Report on the 7th International Congress of IMACSSS and the 4th World Scientific Congress of Sports and Martial Arts - John Arthur Johnson (Universidad de León, 2018)
This report outlines the 7th International Congress of the International Martial Arts and Combat Sports Scientific Society (IMACSSS) and the 4th World Scientific Congress of Sports and Martial Arts (Rzeszow, Poland, October 17-19, 2018) to provide constructive criticism for future conferences. The conference drew numerous scholars from four continents and showcased research on both well-known martial arts and combat sports (e.g., Judo and Taekwondo), while providing a spotlight for less-researched arts (e.g., Malaysia's Silat and various Polish art forms) as well. Presentations were on qualitative and quantitative research and spanned several academic disciplines. While the three-day conference was organized well and expertly run, slight changes to the schedule could maximize participants' overall experience at future IMACSSS events.